2006
DOI: 10.1093/icb/icj034
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotial metamorphosis in filamentous fungi is induced by oxidative stress

Abstract: Sclerotium-forming filamentous fungi are of great agricultural and biological interest because they can be viewed as models of simple metamorphosis. They differentiate by asexually producing sclerotia but the processes involved in sclerotial metamorphosis were poorly understood. In 1997, it was shown for the first time that the sclerotial differentiation state in Sclerotium rolfsii concurred with increasing levels of lipid peroxides. This finding prompted the development of a theory supporting that sclerotial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
127
0
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 118 publications
13
127
0
15
Order By: Relevance
“…For ascomycetes, it has been reported that oxidative stress can induce differentiation (8,16). In full agreement, our analyses using antioxidants show an important decrease in conidiation in response to injury, which, together with the production of ROS by Nox1, indicate that mechanical injury generates oxidative stress, leading to conidiation in T. atroviride.…”
Section: Discussionsupporting
confidence: 90%
“…For ascomycetes, it has been reported that oxidative stress can induce differentiation (8,16). In full agreement, our analyses using antioxidants show an important decrease in conidiation in response to injury, which, together with the production of ROS by Nox1, indicate that mechanical injury generates oxidative stress, leading to conidiation in T. atroviride.…”
Section: Discussionsupporting
confidence: 90%
“…This finding has been supported by other studies that developed into a theory of oxidative stress as an inducer of sclerotial metamorphosis (Georgiou et al, 2006). Specifically, hydroxyl radical scavengers, vitamin C and b-carotene (both also acting as endogenous fungal antioxidants), decreased sclerotial differentiation in S. rolfsii, S. minor, S. sclerotiorum and R. solani.…”
Section: Introductionsupporting
confidence: 74%
“…Oxidative stress has been suggested to be involved in the differentiation of several fungi, including Aspergillus nidulans, N. crassa, Rhizoctonia solani, Sclerotinia sclerotiorum and Sclerotinia minor, and in Sclerotium rolfsii, sclerotial biogenesis in response to mycelial injury occurs as a result of oxidative stress (Aguirre, et al, 2005;Georgiou et al, 2006;Papapostolou & Georgiou, 2010).…”
Section: Mycelial Injurymentioning
confidence: 99%